Influence of Transformational Leadership on the Organizational Performance of TIER-1 Commercial Banks in Nakuru County - Maeri, Joseph Karamu; Kipchumba, Simon; Bowen, Jeptepkeny Chebet (Kabarak University, 2025)
Abstract In a competitive market significantly influenced by rapid digital transfor mation, commercial banks must harness leadership approaches that foster innovation,collaboration,and adaptability.Strategic leadership,particularl y transformational leadership, is critical for navigating the underlying complexities. This study investigated the influence of transformational leadership on the organizational performance of tier-1 commercial banks in Nakuru County, Kenya. Anchored in Complexity Leadership Theory (CLT), the research employed a quantitative approach based on cross sectional survey design. Data was collected from 142 managers across 34 branches of tier-1 banks using a structured questionnaire. Correlation results showed a strong positive correlation between transformational leadership and organizational performance(r=0.562,p < .001). Regression analysis revealed that transformational leadership accounts for 33.4% of the variance in organizational performance (F(3, 138) = 21.293, β = 0.246, p < .05), highlighting its significant positive impact. Visionary leadership, intellectual stimulation, and employee empowerment stood out as influential performance drivers. Therefore, tier-1 banks should consider institutionalizing transformational practices, like promoting autonomy, aligning stakeholders with company vision, and enhancing innovative agendas.
Full text
Keywords: Transformational leadership; tier-1 commercial banks; organizational culture; organizational performance